Utilization of Tissue and Food Coloring in Batik Learning for Early Childhood Education (PAUD) Students - Fifiafianti, Elsy; Gunadi, Gunadi (Universitas Negeri Semarang, 2025)
Early Childhood Education (PAUD) is a level of education preceding primary education, aimed at nurturing children from birth up to six years old. One method of learning batik motifs is through the use of tissue paper and food coloring, which aligns with young children's ability to create artwork. Using a qualitative descriptive approach, this study aims to examine the treatment given to early childhood students to foster their creative potential. The research findings indicate that students show an interest in artistic creation and have the potential for further development, as reflected in their enthusiasm and curiosity through questioning. The learning objectives are achieved when students actively participate in the lessons and produce batik artwork based on their creativity and color preferences. PAUD prioritizes learning through play to support children's creativity and motor skill development in artistic expression, rather than solely focusing on artistic creation itself. Additionally, students can learn about the diversity of batik patterns, predominantly featuring dot motifs, with the aid of tissue paper and food coloring.